The Effect of Silymarin Flavonolignans and Their Sulfated Conjugates on Platelet Aggregation and Blood Vessels Ex Vivo - Pourová, Jana; Applová, Lenka; Macáková, Kateřina; Vopršalová, Marie; Migkos, Thomas; Bentanachs, Roger; Biedermann, David; Petrásková, Lucie; Tvrdý, Václav; Hrubša, Marcel; Karlíčková, Jana; Křen, Vladimír; et al. (Nutrients, 2019)
Silymarin is a traditional drug and food supplement employed for numerous liver disorders. The available studies indicate that its activities may be broader, in particular due to claimed benefits in some cardiovascular diseases, but the contributions of individual silymarin components are unclear. Therefore, we tested silymarin flavonolignans as pure diastereomers as well as their sulfated metabolites for potential vasorelaxant and antiplatelet effects in isolated rat aorta and in human blood, respectively. Eleven compounds from a panel of 17 tested exhibited a vasorelaxant effect, with half maximal effective concentrations (EC50) ranging from 20 to 100 μM, and some substances retained certain activity even in the range of hundreds of nM. Stereomers A were generally more potent as vasorelaxants than stereomers B. Interestingly, the most active compound was a metabolite-silychristin-19-O-sulfate. Although initial experiments showed that silybin, 2,3-dehydrosilybin, and 2,3-dehydrosilychristin were able to substantially block platelet aggregation, their effects were rapidly abolished with decreasing concentration, and were negligible at concentrations ≤100 μM. In conclusion, metabolites of silymarin flavonolignans seem to have biologically relevant vasodilatory properties, but the effect of silymarin components on platelets is low or negligible.
Keywords: inhibitory agregace trombocytů; aorta; agregace trombocytů; Male; molekulární struktura; Molecular Structure; vazodilatancia; mužské pohlaví; Platelet Aggregation; Vasodilator Agents; krysa rodu Rattus; Aorta; Animals; lidé; Humans; zvířata; Rats; Flavonolignans; Platelet Aggregation Inhibitors; flavonolignany